Daya Tarik Influencer, Ulasan Online, dan Pemasaran Digital dalam Mendorong Keputusan Pembelian di Shopee: Perspektif Mahasiswa Fakultas Ekonomi Universitas Muhammadiyah Aceh - Muhammad Hadi Ilyas; Erlinda Erlinda; Marlizar Marlizar (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study uses quantitative analysis methods to examine and analyze the influence of digital marketing, brand influencers, and online customer reviews on purchasing decisions in e-commerce shopee (case study on students of the Faculty of Economics, University of Muhammadiyah Aceh). The population in this study were all students of the Faculty of Economics, the University of Muhammadiyah Aceh who use e-commerce shopee. The research sample was set at 96 customers. The sample size was determined based on the Rao Purba formula. Sampling was carried out using a purposive sampling technique. The primary data was collected by distributing questionnaires. The analysis technique used multiple linear regression. The results showed that online customer reviews and digital marketing had a positive and significant effect on purchasing decisions in e-commerce shopee. Brand influencers did not have a significant effect on purchasing decisions in e-commerce shopee. Furthermore, all variables simultaneously affect purchasing decisions in e-commerce shopee (case study on students of the Faculty of Economics, University of Muhammadiyah Aceh).